Does the introduction of prostate multiparametric magnetic resonance imaging into the active surveillance protocol for localized prostate cancer improve patient re‐classification?. (9th May 2018) - Bryant, Richard J.; Yang, Bob; Philippou, Yiannis; Lam, Karla; Obiakor, Maureen; Ayers, Jennifer; Chiocchia, Virginia; Gleeson, Fergus; MacPherson, Ruth; Verrill, Clare; Sooriakumaran, Prasanna; Hamdy, Freddie C.; et al.
Abstract : Objectives: To determine whether replacement of protocol‐driven repeat prostate biopsy (PB) with multiparametric magnetic resonance imaging (mpMRI) ± repeat targeted prostate biopsy (TB) when evaluating men on active surveillance (AS) for low‐volume, low‐ to intermediate‐risk prostate cancer (PCa) altered the likelihood of or time to treatment, or reduced the number of repeat biopsies required to trigger treatment. Patients and Methods: A total of 445 patients underwent AS in the period 2010–2016 at our institution, with a median (interquartile range [IQR]) follow‐up of 2.4 (1.2–3.7) years. Up to 2014, patients followed a 'pre‐2014' AS protocol, which incorporated PB, and subsequently, according to the 2014 National Institute for Health and Care Excellence (NICE) guidelines, patients followed a '2014–present' AS protocol that included mpMRI. We identified four groups of patients within the cohort: 'no mpMRI and no PB'; 'PB alone'; 'mpMRI ± TB'; and 'PB and mpMRI ± TB'. Kaplan–Meier plots and log‐rank tests were used to compare groups. Results: Of 445 patients, 132 (30%) discontinued AS and underwent treatment intervention, with a median (IQR) time to treatment of 1.55 (0.71–2.4) years. The commonest trigger for treatment was PCa upgrading after mpMRI and TB (43/132 patients, 29%). No significant difference was observed in the time at which patients receiving a PB alone or receiving mpMRI ± TB discontinued AS to undergo treatment (median 1.9 vs 1.33 years; P = 0.747). Considering only those patients who underwent repeat biopsy, a greater proportion of patients receiving TB after mpMRI discontinued AS compared with those receiving PB alone (29/66 [44%] vs 32/87 [37%]; P = 0.003). On average, a single set of repeat biopsies was needed to trigger treatment regardless of whether this was a PB or TB. Conclusions: Replacing a systematic PB with mpMRI ±TB as part of an AS protocol increased the likelihood of re‐classifying patients on AS and identifying men with clinically significant disease requiring treatment. mpMRI ±TB as part of AS thereby represents a significant advance in the oncological safety of the AS protocol.